The Impact of Complementary Cupping Therapy on Immunity Changes (Interleukin-10) in Coastal Fishermen with Hypertension - Indriono Hadi; Lilin Rosyanti; Akhmad Akhmad; Alfi Syahar Yakub (Poltekita: Jurnal Ilmu Kesehatan, 2025)
This study investigated the impact of complementary cupping therapy on immunity changes, specifically interleukin-10 (IL-10) levels, in coastal fishermen with hypertension. Forty participants, aged 20-50 years, were randomly allocated to either a cupping therapy intervention group or a placebo group. Blood pressure, pulse rate, and IL-10 levels were measured before and two weeks after the intervention. The cupping therapy procedure followed a six-step protocol, including informed consent, equipment preparation, point selection, scarification, and post-treatment care. Data were analyzed using paired and independent t-tests. The results showed a significant increase in IL-10 levels (P=0.049) and a significant decrease in systolic and diastolic blood pressure (P<0.05) in the hypertension group receiving cupping therapy. In contrast, no significant changes were observed in the normotensive group. The findings suggest that wet cupping therapy may enhance the immune system by increasing IL-10 levels and lowering blood pressure in hypertensive coastal fishermen. The underlying mechanisms may involve local inflammation, activation of the complement system, increased nitric oxide production, and stimulation of the autonomic nervous system. However, the limited sample size and potential methodological limitations warrant further high-quality trials to confirm these results. The study concludes that wet cupping therapy could serve as a viable complementary treatment for hypertension in fishing communities, but a comprehensive approach considering cultural, religious, and psychological perspectives is necessary to understand its full impact on individuals and society.